Safety Promotion as a Key Element of the Workplace Accident Reduction Strategy in Polish Enterprise - Joanna MICHALIK; Marlena KRAKOWIAK; Dorota WOJTYTO; Szymon BERSKI (Communications of International Proceedings, 2023)
Safety promotion issues belongs to a group of important elements affecting the activities of every organization and are widely discussed among modern scientists and experts. Building a culture of occupational safety translates primarily into a decreasing number of accidents at work and raises the company’s reputation in the market and among the employees. Therefore, a preliminary analysis of the state of occupational health and safety in Poland was made based on statistical data on the number, severity, causes of accidents and occupational diseases – their structure and indicators. The methods of shaping the safety culture in the company, methods of promoting safety and their effectiveness were reviewed. The study was based on data from industry and the Central Statistical Office in Poland. The analysis of the company's health and safety promotion activities and their effects allows to conclude that these efforts bring the desired result.  It can be achieved thanks to perseverance, continuous improvement, multi-level actions and the commitment of both the management and especially employees. The obtained results can be useful for employers and occupational safety and health services due to the importance of unconventional ideas and attitudes and cooperation of all stakeholders in field of work safety.